2022
DOI: 10.1038/s41598-022-10546-9
|View full text |Cite
|
Sign up to set email alerts
|

Melanin is a plenteous bioactive phenolic compound in date fruits (Phoenix dactylifera L.)

Abstract: Date palm fruits (Phoenix dactylifera L.) were found to contain high levels of allomelanin (1.2–5.1%). The melanin is localized in the tanniferous cells between the inner and outer mesocarp tissues of the fruit. The melanin, extracted with 2 M sodium hydroxide, consisted of amorphous graphene-like granular structures of irregular shape and variable size. The date fruit melanin mainly comprises carbon (64.6%) and oxygen (30.6) but no nitrogen, and was thermally stable. It has radical scavenging (63.6–75.1 IC50,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 44 publications
2
19
0
1
Order By: Relevance
“…In contrast to the smoother surface of MelS, ANF has a higher probability of contacting the V‐shaped crevice, leading to a noticeable inhibition of α ‐glucosidase activity. These findings are consistent with previous studies demonstrating the inhibitory effects of eumelanin, as well as other melanin types, on α ‐glucosidase activity 31,32 . Therefore, the ANF eumelanin sample with the most potent enzyme inhibition rate was chosen for subsequent cellular and animal experiments.…”
Section: Resultssupporting
confidence: 90%
“…In contrast to the smoother surface of MelS, ANF has a higher probability of contacting the V‐shaped crevice, leading to a noticeable inhibition of α ‐glucosidase activity. These findings are consistent with previous studies demonstrating the inhibitory effects of eumelanin, as well as other melanin types, on α ‐glucosidase activity 31,32 . Therefore, the ANF eumelanin sample with the most potent enzyme inhibition rate was chosen for subsequent cellular and animal experiments.…”
Section: Resultssupporting
confidence: 90%
“…The FTIR spectrum of the methanolic extracts (Supplementary Figure S1) is also consistent with previous literature (Alam et al, 2022). It has been reported that IR spectrum of dates extracts exhibits multiple peaks responsible for functionalities present in lipid (2,960-2,850 cm −1 ), amide (3,299-3,399 cm −1 and 1,591-1,529 cm −1 for amine and 1,619-1,691 for carbonyl) and carbohydrates (900-1,200 cm −1 ).…”
Section: Resultssupporting
confidence: 90%
“…As it is clear, the IR spectra of M1 and M2 are identical. The spectrum shows a stretching vibrations band at 3,280 cm −1 attributed to -OH group, bands at 2,888 and 2,930 cm −1 attributed to C sp3 -H stretching vibration, aromatic C=C stretching vibrations at 1,622 cm −1 and C-O deformation vibrations of aliphatic alcohols at 1,009 cm −1 (Alam et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…17 High levels of allomelanin are present in date fruits and have a high thermal stability: only 20% weight loss occurs at 220 1C. 89 Pyomelanin produced by Bacillus subtilis and Bacillus thermophilus have mass reduction (three stages): 49 the release of intramolecular or intermolecular water bound to melanin, the decomposition of intermolecular aliphatic groups, and the release of aromatic compounds.…”
Section: Structure Analysismentioning
confidence: 99%
“…53 Lu et al 108 found that melanin in begonia has effects that can inhibit α-glucosidase and PTP1B for the first time. Alam et al 89 found that high levels of allomelanin in date palm fruits ( Phoenix dactylifera L.) had good inhibitory effects on glycosidase and amylase activities.…”
Section: Biological Activities Of Melaninmentioning
confidence: 99%